The Role of Green Human Resource Managemen in Digital-Based Organization : A Systematic Review from 2019 – 2023 - Buhairi (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2025)
Abstract The implementation of Green Human Resource Management (GHRM) practices reflects the awareness of organization and responsibility towards the environment. The aim of this paper is to analyze the relationship between GHRM and digital-based organizations. This research relies on systematic review techniques to analyze scientific production in this field. A total of 33 GHRM articles were extracted using three main levels of analysis. This study reveals that: (i) GHRM management practices can be summarized into four main categories (employees, marketing systems and organizational social responsibility, leadership and management, and organizational behavior and culture); (ii) the importance of GHRM management does not only include environmental objectives; and (iii) there are significant barriers that must be considered when implementing GHRM practices in digital-based organizations. Keywords: Green Human Resource Management; Green organization; Green digital; Green technology; SLR;